Modular Isolated DC-DC Converters for Ultra-Fast EV Chargers: A Generalized Modeling and Control Approach - Mena ElMenshawy (18810244) (2020)
Electric Vehicles (EVs) play a significant role in the reduction of CO2 emissions and other health-threatening air pollutants Accordingly, several research studies are introduced owing to replacing conventional gasoline-powered vehicles with battery-powered EVs. However, the ultra-fast charging (UFC) of the battery pack or the rapid recharging of the battery requires specific demands, including both: the EV battery and the influence on the power grid. In this regard, advanced power electronics technologies are emerging significantly to replace the currently existing gas station infrastructures with the EV charging stations to move from conventional charging (range of hours) to UFC (range of minutes). Among these power electronics conversion systems, the DC-DC conversion stage plays an essential role in supplying energy to the EV via charging the EV’s battery. Accordingly, this paper aims to present possible architectures of connecting multiple Dual Active Bridge (DAB) units as the DC-DC stage of the EV fast charger and study their Small-Signal Modeling (SSM) and their control scheme. These are, namely, Input-Series Output-Series (ISOS), Input-Series Output-Parallel (ISOP), Input-Parallel Output-Parallel (IPOP), and Input-Parallel Output-Series (IPOS). The control scheme for each system is studied through controlling the output filter inductor current such that the current profile is based on Reflex Charging (RC). The main contribution of this paper can be highlighted in providing generalized SSM as well as providing a generalized control approach for the Input-Series Input-Parallel Output-Series Output-Parallel (ISIP-OSOP) connection. The generalized model is verified with three different architectures. The control strategy for each architecture is studied to ensure equal power sharing, where simulation results are provided to elucidate the presented concept considering a three-module ISOS, IPOP, ISOP, and IPOS DC-DC converters. Other Information Published in: Energies License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/en13102540